The Concept of Reconstruction of Cohabitation Regulations in the National Criminal Code Based on the Principle of Legal Certainty - Muntini, Muntini; Suhartono, Slamet; Mangesti, Yovita Arie; Setyorini, Erny Herlin (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
Provisions regarding living together as husband and wife outside of marriage, known as cohabitation, were introduced in Law Number 1 of 2023 concerning the Criminal Code (National Criminal Code). However, the regulation has many problems, including philosophical, sociological and juridical problems, as well as inappropriate norms, not reflecting justice and ignoring religious and customary norms. This research aims to analyze and find a reconstruction of the formulation of cohabitation norms in the National Criminal Code based on principle of legal certainty. The formulation of the problem proposed is How to reconstruct the formulation of cohabitation norms in the National Criminal Code, based on the principle of legal certainty. The research method uses normative legal research, namely a process of finding legal rules, legal principles and legal doctrines to answer the legal issues faced. The approaches used are the statutory approach, the comparative approach and the conceptual approach. Sources of legal materials are primary legal materials, secondary legal materials and tertiary legal materials. The results obtained from this research, Article 412 of the National Criminal Code needs to be reconstructed regarding cohabitation norms, namely living together not as husband and wife because it is not based on a legal marriage, the cohabitation offense is also not a complaint offense but is an ordinary offense, and because cohabitation behavior is not in accordance with The spirit of Pancasila is contrary to religious customs and norms, so we must receive heavier sanctions so that between criminal penalties and fines are accumulative punishments.